Common techniques and methods for screening of natural products for developing of anticancer drugs - Singh M.; Patra S.; Singh R.K. (My University, 2025)
Cancer is a multifaceted disease with different hallmarks. The development procedure of anticancer drugs needs different screening methods and disease models to examine the basic mechanism of action of natural products. At present, more than 60% of anticancer drugs are natural products which are either isolates of plants or their derivatives, indicating the opportunity for new drug development from natural product. The mode of action and targets of different compounds are generally different, leading to a challenge for researcher to elucidate the action and mechanism appropriately. For an anticancer drug development, several experimental procedures are required such as extraction, fractionation, purification, identification and finally evaluation. This procedure is completed through different experimental models and assays such as biochemical characterization, antioxidant assay, anticancer assay, ROS assay, apoptosis assay, cell migration assay, pharmacological assays, computer-based evaluation, etc. The screening and development of anticancer drugs are well discussed in this chapter. © 2021 Elsevier Inc. All rights reserved.